Preparation method of high-conductivity PEDOT: PSS conductive frame

Through physical foaming method and anionic surfactant-induced phase separation method, a high conductivity and low density PEDOT:PSS conductive framework was prepared, which solved the problems of low conductivity and biotoxicity in the prior art, and achieved widespread application in the field of biosensing.

CN119775625AActive Publication Date: 2025-04-08ZHEJIANG UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510112380.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-08
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

In the prior art, the PEDOT:PSS conductive frame has a low conductivity, and the exogenous crosslinking agents and solvents have biotoxicity, which limits its application in the field of biosensing.

Method used

The PEDOT:PSS conductive frame was prepared by physical foaming method, and the PEDOT:PSS phase was separated by adding anionic surfactant to form a porous structure with high porosity and high interconnectivity, avoiding the use of high-strength acids and biotoxic solvents.

Benefits of technology

The PEDOT:PSS conductive frame with high conductivity (50S/cm-1000S/cm) has been prepared, with good water/oil stability, low modulus and high tensileability, and is green and safe, suitable for the field of biosensing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775625A_ABST
    Figure CN119775625A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-conductivity PEDOT: PSS conductive frame. The preparation method comprises the following steps: filtering a PEDOT: PSS aqueous solution; adding an anionic surfactant to separate the PEDOT: PSS phase and reduce the surface activity of the solution to obtain a mixed solution; adding the mixed solution and air into a double-injector mixing container according to a preset proportion, and mixing and shearing to obtain a PEDOT: PSS foam emulsion; adding the obtained foam emulsion into a specific template and waiting for slow curing; washing the cured PEDOT: PSS foam with water to remove the surfactant and part of PSS; and finally, freeze-drying to remove moisture to obtain the high-conductivity PEDOT: PSS conductive frame. The PEDOT: PSS conductive frame prepared by the invention has excellent water / oil stability, higher conductivity, lower frame density and more excellent mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of conductive material preparation, and in particular relates to a method for preparing a PEDOT:PSS conductive frame with high conductivity. Background Art

[0002] In recent years, conductive framework materials have attracted great attention from academia and industry due to their potential applications in tissue engineering, sensors, etc. The conductive components in conductive framework materials mainly include metal-based or carbon-based materials and conductive polymer materials. Compared with metal and carbon-based materials, conductive polymer materials (such as polyaniline, poly(3,4-ethylenedioxythiophene:polystyrene sulfonate (PEDOT:PSS), polypyrrole) have a Young's modulus that is more consistent with biological tissues, better stretchability, more diverse processing methods and adjustable conductivity, and are considered to be ideal materials for constructing conductive frameworks.

[0003] Among them, PEDOT:PSS conductive frameworks have been widely studied due to their high conductivity and excellent chemical and environmental stability. PEDOT:PSS conductive frameworks are usually made from commercially available PEDOT:PSS dispersions by introducing a crosslinker into the dispersion and then freeze-drying. However, exogenous crosslinkers are not conducive to the removal of non-conductive PSS components and the rearrangement of conductive PEDOT chains, limiting the conductivity of the resulting PEDOT:PSS conductive framework (usually less than 100S / m). In the prior art, post-treatment with proton acid or co-solvent is the main method to improve the various properties of PEDOT:PSS conductive frameworks. These treatments can weaken the ionic bond between PEDOT and PSS, allowing the PEDOT-rich structure to be physically interconnected under the action of π-π stacking. Combined with high-temperature annealing methods, the non-conductive PSS chains can be further separated, further improving the conductivity of the conductive framework. However, the solvents introduced in these technologies have certain biological toxicity, which is not conducive to their further application in the field of biosensing. In addition, the PEODT:PSS conductive framework structure prepared by freeze-drying has closed pores and mechanical brittleness, which will further cause the conductive framework structure to shrink and be destroyed after post-processing steps.

[0004] Therefore, it is still necessary to develop a method for preparing a low-density, highly interconnected pores and high-conductivity PEDOT:PSS conductive framework. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for preparing a PEDOT:PSS conductive framework with high electrical conductivity.

[0006] To achieve the above object, the present invention adopts the following technical solution:

[0007] A method for preparing a PEDOT:PSS conductive framework with high electrical conductivity, comprising:

[0008] Step S1, filtering the PEDOT:PSS aqueous solution; adding anionic surfactant to separate the PEDOT:PSS phases and reduce the surface activity of the solution to obtain a mixed solution;

[0009] Step S2, adding the mixed solution and air into a double syringe mixing container in a predetermined ratio, mixing and shearing to obtain a PEDOT:PSS foam emulsion;

[0010] Step S3, adding the obtained foam emulsion into a specific template and waiting for it to slowly solidify;

[0011] Step S4, washing the solidified PEDOT:PSS foam with water to remove the surfactant and part of PSS;

[0012] Step S5, freeze-drying to remove moisture to obtain a high-conductivity PEDOT:PSS conductive framework.

[0013] Preferably, in step S1, the mass fraction of the anionic surfactant relative to the mixed solution is 0.01 wt%-10 wt%.

[0014] Preferably, in step S2, the mixed solution and air are added into a double syringe mixing container, wherein the volume of air accounts for 30%-90% of the total volume of gas and liquid, and the piston is repeatedly pushed and pulled to obtain the PEDOT:PSS foam emulsion.

[0015] Preferably, in step S1, the original PEDOT:PSS solution is passed through a water filter to be prepared into a 0.1-5 wt % aqueous solution.

[0016] Preferably, a surfactant is used as a foaming agent to form a porous structure, and the surfactant in step S1 mainly includes anionic surfactants and neutral surfactants; wherein the anionic surfactants include: 10-hexadecylbenzenesulfonic acid, 10-hexadecyl sodium sulfate, 10-hexadecyl sodium sulfonate; the neutral surfactants include: polyethylene glycol, polyvinyl alcohol surfactants.

[0017] Preferably, in step S2, the double syringe mixing treatment time is 2-60 min.

[0018] Preferably, in step S3, the material is slowly cured at room temperature, and the curing time is 20 minutes to 10 hours.

[0019] Preferably, in step S4, the washing times are 2-3 times, and the soaking time each time is 0.5-1h.

[0020] Preferably, the prepared PEDOT:PSS conductive framework has an electrical conductivity of 50S / cm-1000S / cm.

[0021] The present invention has the following advantages:

[0022] 1. The present invention adopts a physical foaming method, which is simple to operate. The prepared frame has controllable pores, low density, interconnected pores and high stretchability.

[0023] 2. The present invention uses anionic surfactants to induce physical crosslinking caused by PEDOT:PSS phase separation, and has good water / oil stability, low modulus and high conductivity.

[0024] 3. The present invention does not use high-strength acids such as sulfuric acid and biotoxic organic solvents for post-treatment. The prepared conductive framework is green, safe and has good biocompatibility, and has broad application prospects in the field of in vivo and in vitro biosensing. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0026] Figure 1 This is a flow chart of a method for preparing a PEDOT:PSS conductive framework with high electrical conductivity according to an embodiment of the present invention;

[0027] Figure 2 This is a scanning electron microscope photo of the PEDOT:PSS porous framework of the present invention;

[0028] Figure 3 The present invention is a PEDOT:PSS porous framework porosity comparison diagram and a pore size statistical diagram comparison data diagram, (a) is a PEDOT:PSS porous framework porosity comparison diagram, (b) is a pore size statistical diagram comparison data diagram;

[0029] Figure 4 This is a conductivity comparison diagram of the PEDOT:PSS porous framework of the present invention;

[0030] Figure 5 The mechanical characterization of the PEDOT:PSS porous framework of the present invention, (a) is a compressive strain data diagram of the conductive framework prepared by the present invention, (b) is a compressive strain data diagram of the conductive framework prepared by the traditional freeze-drying method;

[0031] Figure 6This is a data diagram of the long-term stability of the PEDOT:PSS porous framework of the present invention in PBS. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0034] like Figure 1 As shown, the embodiment of the present invention provides a method for preparing a highly conductive PEDOT:PSS conductive frame

[0035] Step 1: Filter the PEDOT:PSS aqueous solution through a water filter, add an anionic surfactant to the PEDOT:PSS aqueous solution mixed solution, the mass fraction of the anionic surfactant relative to the mixed solution is 0.01wt%-10wt%

[0036] Step 2: Add the mixed solution and air into a double syringe mixing container, wherein the volume of air accounts for 30%-90% of the total volume of gas and liquid, to obtain a PEDOT:PSS foam emulsion, and the mixing treatment time is 2-10 minutes.

[0037] Step 3: Add the prepared foam emulsion to the template solution, the surfactant induces PEDOT:PSS phase separation, physical cross-linking occurs between PEDOT molecules, and slowly solidifies at room temperature, with a curing time of 20 minutes to 10 hours.

[0038] Step 4, washing and soaking the solidified PEDOT:PSS skeleton in water for 2-3 times, each time for 0.5h-1h, to remove the surfactant and PSS;

[0039] Step 5. Finally, freeze-dry to obtain a high-conductivity PEDOT:PSS conductive framework.

[0040] The present invention will be further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.

[0041] Example 1: A method for preparing a highly conductive PEDOT:PSS conductive skeleton, comprising the following steps:

[0042] (1) filtering the PEDOT:PSS aqueous solution through a water filter, adding dodecylbenzenesulfonic acid to the mixed solution of the PEDOT:PSS aqueous solution, wherein the mass fraction of the dodecylbenzenesulfonic acid relative to the mixed solution is 5 wt %;

[0043] (2) adding the mixed solution and air into a double syringe mixing closed container, wherein the volume of air accounts for 50% of the total volume of gas and liquid, and rapidly mixing for 4 minutes to obtain a PEDOT:PSS foam emulsion;

[0044] (3) adding the obtained foam emulsion to the template solution, and slowly solidifying at room temperature by inducing the phase separation of PEDOT:PSS with the surfactant for 10 h;

[0045] (4) washing and soaking the solidified porous framework with water for 2-3 times, each time with an interval of 0.5 h, to remove the surfactant and PSS;

[0046] (5) Finally, freeze-drying is performed to remove moisture to obtain a high-conductivity PEDOT:PSS conductive framework.

[0047] Example 2

[0048] (1) Step (1) is the same as step (1) of Example 1;

[0049] (2) adding the mixed solution and air into a double syringe mixing closed container, wherein the volume of air accounts for 60% of the total volume of gas and liquid, and rapidly mixing for 4 minutes to obtain a PEDOT:PSS foam emulsion;

[0050] (3) Steps (3) to (5) are the same as steps (3) to (5) in Example 1.

[0051] Example 3

[0052] (1) Step (1) is the same as step (1) of Example 1;

[0053] (2) adding the mixed solution and air into a double syringe mixing container, wherein the volume of air accounts for 70% of the total volume of gas and liquid, and rapidly mixing for 4 minutes to obtain a PEDOT:PSS foam emulsion;

[0054] (3) Steps (3) to (5) are the same as steps (3) to (5) in Example 1.

[0055] Example 4

[0056] (1) Step (1) is the same as step (1) of Example 1;

[0057] (2) adding the mixed solution and air into a double syringe mixing closed container, wherein the volume of air accounts for 80% of the total volume of gas and liquid, and rapidly mixing for 4 minutes to obtain a PEDOT:PSS foam emulsion;

[0058] (3) Steps (3) to (5) are the same as steps (3) to (5) in Example 1.

[0059] Example 5

[0060] (1) Step (1) is the same as step (1) of Example 1;

[0061] (2) adding the mixed solution and air into a double syringe mixing closed container, wherein the volume of air accounts for 90% of the total volume of gas and liquid, and rapidly mixing for 4 minutes to obtain a PEDOT:PSS foam emulsion;

[0062] (3) Steps (3) to (5) are the same as steps (3) to (5) in Example 1.

[0063] Comparative Example 1: A method for preparing a PEDOT:PSS conductive framework by freeze-drying, comprising:

[0064] (1) PEDOT:PSS aqueous solution is filtered through a water filter;

[0065] (2) Freezing the filtered PEDOT:PSS solution in a refrigerator and then freeze-drying it to obtain a PEDOT:PSS conductive framework.

[0066] Figure 2 This is a scanning electron microscope (SEM) photo of the PEDOT:PSS porous framework of the present invention. It can be seen that the foam-processed PEDOT:PSS porous framework of the present invention presents a macroscopic and microscopic interconnected porous structure. The conductive polymer PEDOT:PSS condenses into uniform macroscopic circular holes along the gaps between bubbles. The PEDOT:PSS after condensation in the gaps presents surrounding small holes under the guidance of the ice template. With the increase of the gas volume fraction, the solution in the gaps between the foams is reduced and the foams are more easily coarsened, and the circular holes formed have thinner walls and larger pores. The freeze-dried PEDOT:PSS presents a loose and chaotic non-interconnected porous structure.

[0067] Figure 3 A and Figure 3b is a comparison chart of the porosity of the PEDOT:PSS porous framework of the present invention and a comparison chart of the pore size statistics. As the gas volume fraction increases, the pores of the PEDOT:PSS porous framework first increase and then remain at >99%. This is because, as the gas volume fraction increases, the solid density of the framework decreases, resulting in an increased porosity. However, the low solid density of the framework causes the framework to collapse during the preparation process because it cannot support the framework morphology. As the gas volume fraction increases, the average pore size of the PEDOT:PSS porous framework shows a linear increase trend, with a minimum of 50μm and a maximum of 260μm.

[0068] Figure 4 The conductivity comparison diagram of the PEDOT:PSS porous framework of the present invention is shown in FIG. By introducing anionic surfactants, the PEDOT:PSS porous framework has a higher conductivity, and the conductivity of the obtained PEDOT:PSS porous framework can reach up to 800S / cm, while the conductivity of the PEDOT:PSS porous framework without the introduction of anionic surfactants is 0.5S / cm. This is because the addition of anionic surfactants causes phase separation of PEDOT:PSS, so that part of the PSS chain is separated from the PEDOT chain, and the PEDOT-rich structure is physically interconnected under the action of π-π stacking to form a new conductive path, thereby obtaining a higher conductivity.

[0069] Figure 5 For the mechanical characterization of the PEDOT:PSS porous framework of the present invention, Figure 5 a is the compression strain data of the conductive frame prepared in Example 3. It can be seen that after 500 compression cycles, the maximum stress did not drop significantly and maintained good resilience, indicating that the PEDOT:PSS porous frame prepared by the present invention has excellent mechanical properties and fatigue resistance. However, the conductive frame prepared by the conventional freeze-drying method undergoes obvious plastic deformation after the first compression. After 500 compression cycles, the maximum stress of the frame drops significantly. Figure 5 As shown in b.

[0070] Figure 6 This is a data graph of the long-term stability of the PEDOT:PSS porous framework of the present invention in PBS. The PEDOT:PSS porous framework of the present invention can maintain long-term stability in an aqueous environment. We stored it in PBS for 28 days and tested its charge injection ability on the 1st day, the 7th day, and the 28th day. It can be seen that the charge injection ability of the PEDOT:PSS porous framework of the present invention did not decrease significantly after 28 days, indicating that the PEDOT:PSS porous framework of the present invention has good water stability.

[0071] The embodiments described above are only descriptions of the preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a high-conductivity PEDOT:PSS conductive framework, characterized in that: include: Step S1, filtering the PEDOT:PSS aqueous solution; adding anionic surfactant to separate the PEDOT:PSS phases and reduce the surface activity of the solution to obtain a mixed solution; Step S2, adding the mixed solution and air into a double syringe mixing container in a predetermined ratio, mixing and shearing to obtain a PEDOT:PSS foam emulsion; Step S3, adding the obtained foam emulsion into a specific template and waiting for it to slowly solidify; Step S4, washing the solidified PEDOT:PSS foam with water to remove the surfactant and part of PSS; Step S5, freeze-drying to remove moisture to obtain a high-conductivity PEDOT:PSS conductive framework.

2. The method for preparing a PEDOT:PSS conductive framework with high electrical conductivity as claimed in claim 1, characterized in that: In step S1, the mass fraction of the anionic surfactant relative to the mixed solution is 0.01wt%-10wt%.

3. The method for preparing a PEDOT:PSS conductive framework with high electrical conductivity as claimed in claim 2, characterized in that: In step S2, the mixed solution and air are added into a double syringe mixing container, wherein the volume of air accounts for 30%-90% of the total volume of gas and liquid, and the piston is repeatedly pushed and pulled to obtain a PEDOT:PSS foam emulsion.

4. The method for preparing a PEDOT:PSS conductive framework with high electrical conductivity as claimed in claim 3, characterized in that: In the step S1, the original PEDOT:PSS solution is passed through a water filter to be prepared into a 0.1-5 wt % aqueous solution.

5. The method for preparing a PEDOT:PSS conductive framework with high electrical conductivity as claimed in claim 4, characterized in that: A porous structure is formed by using a surfactant as a foaming agent, wherein the surfactant in step S1 mainly includes anionic surfactants and neutral surfactants; wherein the anionic surfactants include: 10-hexadecylbenzenesulfonic acid, 10-hexadecyl sodium sulfate, 10-hexadecyl sodium sulfonate; and the neutral surfactants include: polyethylene glycol and polyvinyl alcohol surfactants.

6. The method for preparing a PEDOT:PSS conductive framework with high electrical conductivity as claimed in claim 5, characterized in that: In step S2, the double-syringe mixing treatment time is 2-60 minutes.

7. The method for preparing a PEDOT:PSS conductive framework with high electrical conductivity as claimed in claim 6, characterized in that: In the step S3, the solidification is carried out slowly at room temperature, and the solidification time is 20 minutes to 10 hours.

8. The method for preparing a PEDOT:PSS conductive framework with high electrical conductivity as claimed in claim 7, characterized in that: In step S4, the washing times are 2-3 times, and the soaking time each time is 0.5-1h.

9. The method for preparing a PEDOT:PSS conductive framework with high electrical conductivity as claimed in claim 8, characterized in that: The conductivity of the prepared PEDOT:PSS conductive framework is 50S / cm-1000S / cm.

Citation Information

Patent Citations

  • High-conductivity PEDOT: PSS film and preparation method thereof

    CN116693908A

  • High-elasticity PEDOT: PSS aerogel as well as preparation method and application thereof

    CN118307836A

  • Method for Cylinder Demand Air Flow Based On System Cooperation Control and Hybrid Vehicle Thereof

    KR1020200144174A